Complex studies on gene polymorphisms of MMP2, MMP3, MMP9 matrix metalloproteinases and TIMP1, TIMP2 tissue inhibitors of metalloproteinases in the patients with primary open-angle glaucoma - A. V. Shevchenko; V. F. Prokofiev; V. I. Konenkov; V. V. Chernykh; O. V. Ermakova; A. N. Trunov (Медицинская иммунология, 2023)
Abnormal expression of matrix metalloproteinases (MMP) in watery moisture in patients with glaucoma may affect regulation of intraocular pressure (IOP). MMP activity is regulated by tissue metalloproteinase inhibitors (TIMP). The imbalance between tissue metalloproteinase inhibitors and matrix metalloproteinases may contribute to the development of glaucoma. Genetic factors, including polymorphism of matrix metalloproteinase genes and their inhibitors genes, can regulate the level of their expression, thereby affecting susceptibility to disease. Our aim was to perform comprehensive analysis of the MMP2 (rs243865), MMP3 (rs3025058), MMP9 (rs3918242) polymorphisms, and TIMP1 (rs4898), TIMP2 (rs8179090) tissue inhibitor genes polymorphisms in the patients with stage II (advanced) primary open-angle glaucoma.99 patients (52 men and 47 women) with a verified diagnosis of stage II primary open-angle glaucoma were examined. The comparison group consisted of 100 age-matched persons (81 women and 19 men) without ophthalmic disorders. The single-nucleotide polymorphisms in promoter regions of MMP2, TIMP1, TIMP2 genes were analyzed by the TaqMan method, the MMP3 and MMP9 genes, by means of restriction fragment length polymorphism technique. Statistical evaluation was carried out using the specialized package of IBM SPSS Statistics 23 programs. The critical level of significance was assumed to be 0.05.The differences in the distribution of MMP2 rs243865 allelotypes with decreased frequency of TT genotype were found in the patient group and, vice versa, increased heterozygosity rates were revealed among them. In addition, the frequency of TIMP1 rs4898 heterozygous genotype was decreased in this group as compared to control sample. Four MMP/TIMP complex genotypes are positively associated with the development of pathology. Two of them were of bilocus type, i.e., MMP2-1306TC:TIMP2-418GG, and MMP3-11715A6A:TIMP1 372CC whereas two three-locus constellations were revealed, i.e., MMP2-1306TC:MMP9-1562CC:TIMP2- 418GG, and MMP3-11715A6A:MMP9-1562CC:TIMP1 372CC. There are nine MMP/TIMP complexes, the frequency of which in patients with glaucoma was significantly reduced when compared with control group.Polymorphism of regulatory regions of MMP2, MMP3, MMP9 genes and distinct gene variants of their inhibitors (TIMP1, TIMP2 genes) can be considered potential markers of the POAG development associated with an imbalance of MMP/TIMP activities.